1988
DOI: 10.1111/j.1471-4159.1988.tb02925.x
|View full text |Cite
|
Sign up to set email alerts
|

Choline Acetyltransferase Activity in the Rat Brain Cortex Homogenate, Synaptosomes, and Capillaries After Lesioning the Nucleus Basalis Magnocellularis

Abstract: Stereotaxic lesions of the nucleus basalis magnocellularis were made unilaterally in male Wistar rats with either kainic or ibotenic acid, using the contralateral side as control. Differences in behavior, body weight, and survival were observed between the kainic and ibotenic acid-treated rats. One week after surgery, the rats were sacrificed and the effect of the lesions on choline acetyltransferase activity was measured in brain cortex homogenate, synaptosomes, and capillaries. In kainic acid-lesioned rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Our finding of a lack of effect of nucleus basalis lesions on cortical blood flow is in line with the observations of Santos-Benito et al (1988). These authors reported that the ChAT activity associated with cortical microvessels was not affected by lesions of the nucleus basalis in spite of a significant decrease in whole tissue ChAT activity.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of a lack of effect of nucleus basalis lesions on cortical blood flow is in line with the observations of Santos-Benito et al (1988). These authors reported that the ChAT activity associated with cortical microvessels was not affected by lesions of the nucleus basalis in spite of a significant decrease in whole tissue ChAT activity.…”
Section: Discussionsupporting
confidence: 92%